Complementary Coded Scrambling Multiple Access and Its Performance in Downlink MIMO Channels - Liu, Xiqing; Syu, Hong-Ming; Chen, Hsiao-Hwa; Meng, Weixiao; Wei, Meng (IEEE transactions on wireless communications, 2018)
In a traditional complementary coded CDMA (CC-CDMA) system, signals are spread using the direct sequence (DS) technique to suppress multipath interference (MI) and multiple access interference (MAI). However, DS spreading suffers from very poor bandwidth efficiency. This paper proposes a scrambling-based CC-CDMA system, namely complementary coded scrambling multiple access (CCSMA). A CCSMA system offers a unified platform to integrate CC-CDMA, multiple-input multiple-output (MIMO), and scrambling technique seamlessly. Utilizing complementary codes in scrambling modulation, a CCSMA system is able to suppress MI and MAI effectively. With the help of space domain scrambling, the CCSMA system offers much higher bandwidth efficiency than a CC DS-CDMA system. Bit error rate and system capacity are evaluated explicitly in this paper, verifying that CCSMA is a viable multiple access technique for providing high capacity in downlink MIMO channels.